The Effect of Perceived Stress Dimensions on Self-Efficacy and Job Burnout of Public School Teachers - Cetin, Canan; Dede, Ezgi (Archives of Business Research, 2018)
The aim of this study is to investigate the effects of dimensions of perceived stress levels on teachers’ perceived self- efficacy and burn-out. A total of 301 elementary, middle and high public-school teachers were selected randomly as participants in this research. Data were collected by using the Perceived Stress Scale, Teachers’ Sense of Efficacy Scale (TSES) and Maslach Burnout Inventory for educators. In result of analyzing data it is determined that all included opinions extent of teachers’ perceived stress/discomfort scale is medium, insufficient self-efficacy stress scale is low, self-efficacy scale is medium and job burnout scale is low levels. The results revealed that perceived stress dimensions were significantly correlated with self-efficacy and job burnout. There was a negative and meaningful relationship between perceived insufficient self-efficacy sense and self-efficacy and a positive and meaningful relationship between perceived insufficient self-efficacy sense and job burnout. In addition, there was a negative and meaningful relationship between perceived stress / discomfort and self-efficacy and a positive and meaningful relationship between perceived stress / discomfort and job burnout. Finally, structural equation modeling indicated that there was a negative and meaningful relationship between self-efficacy and job burnout.